Penyuluhan jus buah apel dan air dugan sebagai MP-ASI di Posyandu Garuda, Pidada Panjang - Purnama, Robby Candra; Yuniar, Intan Aprelia; Zein , Meilani; Agustina, Risma Eka; Hafidz , M Luthfi (JOURNAL OF Public Health Concerns, 2022)
Background: Complementary food for breast milk is food or drink that contains nutrients given to children to meet their nutritional needs. Apples or in the Latin name Malus domestica are very good for toddlers as a drink (juice) to replace breast milk, this is because besides being delicious, apples have many health benefits for babies. This apple juice has several health benefits for babies, namely improving digestion, treating dysentery, relieving coughs, and nourishing the body. Coconut water or the Latin name Cocos nucifera is highly recommended as a baby's first drink after the baby has completed the journey of exclusive breastfeeding for 6 months. The various nutrients and properties contained in coconut water make it worthy to be called the second best drink after breast milk. Coconut water contains monolaurin, a substance from lauric acid that can build immunity and maintain the health of your little one. Purpose: To further improve the health of children under five and under-fives, as well as to maintain the growth and development of children during their growth period. Methods: In this community service activity the respondents are all mothers who have children under five and toddlers in the area of Posyandu Garuda, Panjang District. This activity uses poster media as a means of presenting material that can be read and taken home for respondents. Result: Counseling on complementary drinks made from apple juice and coconut water in the working area of ​​the Garuda Posyandu went well. Around 50 participants attended. This counseling is expected to increase knowledge of the quality of health to the community so that many toddlers and under-fives are guaranteed nutrition and nutrition. Conclusion: There is an increase in knowledge of breastfeeding mothers or mothers who have toddlers about the importance of consuming breast milk substitutes, who initially did not know the efficacy of apple juice and coconut water. Pendahuluan: Makanan pendamping ASI merupakan makanan atau minuman yang mengandung gizi diberikan kepada anak untuk memenuhi kebutuhan gizinya. Buah Apel atau dalam nama latin Malus domestica sangat baik dikonsumsi balita sebagai  minuman (jus) pengganti asi, hal ini karena selain lezat, apel memiliki banyak manfaat kesehatan untuk bayi. Jus apel ini memiliki beberapa manfaat bagi kesehatan pada bayi yaitu melancarkan pencernaan, mengobati disentri, meredakan batuk, dan menyehatkan tubuh. Air dugan atau nama latin Cocos nucifera sangat disarankan sebagai miuman pertama bayi setelah bayi menuntaskan perjalanan ASI eksklusif selama 6 bulan. Berbagai nutrisi dan khasiat yang terkandung di dalam air kelapa membuatnya layak untuk disebut sebagai minuman terbaik kedua setelah ASI. Air dugan mengandung monolaurin, zat dari asam laurat yang dapat membangun kekebalan tubuh serta menjaga kesehatan Si Kecil. Tujuan: Untuk lebih meningkatkan kesehatan anak balita dan baduta, serta menjaga tumbuh kembang anak dikala masa pertumbuhan. Metode: Dalam kegiatan pengabdian masyarkat ini respondennya adalah seluruh ibu yang memiliki  baduta dan balita yang berada diwilayah Posyandu Garuda Kecamatan Panjang, Kegiatan ini menggunakan media poster sebagai sarana mempersentasikan materi yang dapat dibaca dan dibawa pulang bagi responden. Hasil: Penyuluhan tentang minuman pendamping asi dari jus buah apel dan air kelapa diwilayah kerja posyandu Garuda berjalan dengan lancar. Peserta yang hadir sekitar 50 responden, dengan di adakan penyuluhan ini diharapkan dapat meningkatkan pengetahuan mutu kesehatan kepada masyarakat agar banyak balita dan baduta yang terjamin gizi dan nutrisi nya. Simpulan: Adanya peningkatan pengetahutan ibu menyusui atau ibu yang mempunyai balita tentang pentinganya mengonsumsi minuman pengganti asi, yang awalnya tidak mengetahui khasiat dari jus buah apel dan air buah kelapa saat ini lebih memahami.